La salud pública y las metáforas sobre la vida (2000)
ABSTRACT: As a professor of Public Health in the United States, the author presents her perspective of violence as a public health issue in Colombia, based on her experiences over a relatively short period of time as a Fulbright scholar in Bogota. Though not claiming to be definitive, the article presents the far-ranging complexity of the violence, from its epidemiology, to its social-economic-political origins, and its devastating psychological, social and life threatening consequences over multiple generations. The article is both narrative of experiences with scholars, people in communities, fellow parents, activists, and professionals, as well as a scholarly treatise to illustrate that the violence is not chaotic and indecipherable, but has systematic roots and therefore systematic opportunities for amelioration. Hope for Colombia is uncovered through the dedication of professionals engaged in community development efforts; through existing, though fragile, political negotiations; and through popular demonstrations for peace.